2009
DOI: 10.1143/jjap.48.07gm04
|View full text |Cite
|
Sign up to set email alerts
|

Application of Novel Ultrasonic Cleaning Equipment Using Waveguide mode for Post-Chemical-Mechanical-Planarization Cleaning

Abstract: In this paper, we propose the application of novel ultrasonic cleaning equipment using a waveguide mode, which we called the Megatube, to post chemical mechanical planarization (CMP) cleaning. Waveguides can be created in a curved shape, and ultrasonic waves of 1 MHz, within the megasonic frequency range, can propagate along such waveguides. It is possible to supply ultrasonic waves at a distance from the equipment, which has the advantage of enabling ultrasonic emission in a narrow space. For single-wafer pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We previously proposed waveguide-type ultrasonic cleaning equipment that uses a quartz glass tube as the ultrasonic irradiator. 4,5) We estimated the acoustic amplitude irradiated from the waveguide side to be over 100 kPa, and we showed that the vibration velocity distribution of the waveguide side had a traveling wave distribution. 6) In a traveling ultrasonic wave field, bubbles receive radiation force in the traveling direction, and this force is expected to prevent the collapse of bubbles trapped at pressure antinodes.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We previously proposed waveguide-type ultrasonic cleaning equipment that uses a quartz glass tube as the ultrasonic irradiator. 4,5) We estimated the acoustic amplitude irradiated from the waveguide side to be over 100 kPa, and we showed that the vibration velocity distribution of the waveguide side had a traveling wave distribution. 6) In a traveling ultrasonic wave field, bubbles receive radiation force in the traveling direction, and this force is expected to prevent the collapse of bubbles trapped at pressure antinodes.…”
Section: Introductionmentioning
confidence: 95%
“…If the inner diameter 2a of the waveguide tube is larger than the wavelength w of ultrasonic waves in water, that is, if a is outside the range that creates a plane wave mode (a 0:3 w ), then some ultrasonic waves are reflected at the waveguide. This reflection creates a waveguide mode 5) that depends on the inner diameter of the waveguide tube, and the waveguide vibrates as a Lamb wave. At the waveguide end, ultrasonic energy is absorbed into the propagation water, and the traveling wave component increases.…”
Section: Waveguide-type Ultrasonic Cleaning Equipmentmentioning
confidence: 99%
“…Figure 6 shows the breaking of blood clot in an ultrasonic cleaning bath (MRS ultrasonic cleaner DC150H). The bath generates 40 kHz acoustic wave, which is used to clean the glassware and disperse chemicals based on the principle of cavitation [26]. No visible cavitation bubbles are observed because the bubbles are too small and the energy is not focused.…”
Section: Acoustic Field At the Vibration Tipmentioning
confidence: 99%
“…When ultrasound is irradiated onto liquid, physical and chemical effects occur due to vibration, cavitation, and streaming. These characteristics of ultrasound are applied to cleaning, [1][2][3] homogenization, atomization 4) and chemical reactions. 5,6) Recently, Li et al 7) have reported that the enzymatic hydrolysis of cellulose is enhanced by ultrasonic irradiation.…”
mentioning
confidence: 99%